2004
DOI: 10.1016/j.jcsr.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on stainless steel hollow sections—Part 1: Material and cross-sectional behaviour

Abstract: Basic material properties and cross-sectional data (stress-strain curves and load-end shortening curves) are presented for square, rectangular and circular hollow section specimens in Grade 1.4301 stainless steel. The material tests cover flat material in tension and in compression as well as corner material in tension. Modifications to the Ramberg-Osgood representation are suggested to ensure a close fit to both tensile and compressive behaviour over the full range of strains of interest. Results, including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
216
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 381 publications
(247 citation statements)
references
References 10 publications
2
216
0
Order By: Relevance
“…The specimens were loaded between the two parallel end platens of the testing machine and four displacement transducers (LVDTs) were employed to measure average end-shortening. A similar testing arrangement has been successfully employed in previous studies [7,13]. Uniformity of corner strains (variation between strains at any corner from the average strain being less than 5%) at low load levels confirmed that the specimens were loaded concentrically.…”
Section: Stub Column Testsmentioning
confidence: 72%
See 2 more Smart Citations
“…The specimens were loaded between the two parallel end platens of the testing machine and four displacement transducers (LVDTs) were employed to measure average end-shortening. A similar testing arrangement has been successfully employed in previous studies [7,13]. Uniformity of corner strains (variation between strains at any corner from the average strain being less than 5%) at low load levels confirmed that the specimens were loaded concentrically.…”
Section: Stub Column Testsmentioning
confidence: 72%
“…The experimental set-up for the imperfection measurements employed in the present study was similar to that adopted by Schafer and Peköz [8] and Gardner and Nethercot [13] -each specimen was mounted on the bed of a milling machine where the flat surface provided a reference plane for the measurements. A displacement transducer, fitted in the head of the milling machine, was positioned at the centreline of each face of the specimen and driven along the length.…”
Section: Geometric Imperfection Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted material model is a compound Ramberg-Osgood [33,34] formulation, with the second stage of the model utilising the 1.0% proof stress σ1.0. Two-stage material models for stainless steel have been developed and studied by a number of authors [22,[35][36][37][38]. The material parameters given in Tables 1 and 2 were averaged for each nominal cross-section size and applied uniformly to each model in the true stress true -log plastic strain pl ln  format, as required by ABAQUS [32] and defined by Eqs.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…the yield strength) on the stress level that can be attained by a cross-section. Despite the absence of such a limit for stainless steel, due to the rounded nature of its material response [35][36][37]43], the same approach is followed by Eurocode 3: Part 1.4 [17] for the treatment of local buckling in stainless steel elements, so that consistency between carbon steel and stainless steel design is maintained.…”
Section: Cross-section Classificationmentioning
confidence: 99%